Violence and the breakdown of the political settlement: an uncertain future for Bangladesh?. Issue 3 (4th May 2017) - Hassan, Mirza; Nazneen, Sohela
Abstract: We explore the dynamics of the elite political settlement in Bangladesh after the democratic transition in 1991 and its impact on the elite interactions in the arena of competitive electoral democracy. We trace the history of how a political settlement around regime succession developed in the mid-1990s, and then experienced difficulties in multiple stages, and finally broke down in 2011. Violence was instrumentally used, by the ruling elites and the main opposition party, to influence the processes of negotiations around the succession of power. We argue that 'partyarchy'—where political parties exert informal control of the party through formal processes and institutions—and dynastic rule prevent the political elites from reaching a stable settlement around regime succession. We also show how the changes to the rules of the game around regime succession have led to a qualitative shift in the extent and nature of violence in the political domain, and explore why democratic consolidation remains elusive.